The Enterococcus faecalis fsr Two-Component System Controls Biofilm Development through Production of Gelatinase - Hancock, Lynn E. (American Society for Microbiology, 2004)
Bacterial growth as a biofilm on solid surfaces is strongly associated with the development of human infections. Biofilms on native heart valves (infective endocarditis) is a life-threatening disease as a consequence of bacterial resistance to antimicrobials in such a state. Enterococci have emerged as a cause of endocarditis and nosocomial infections despite being normal commensals of the gastrointestinal and female genital tracts. We examined the role of two-component signal transduction systems in biofilm formation by the Enterococcus faecalis V583 clinical isolate and identified the fsr regulatory locus as the sole two-component system affecting this unique mode of bacterial growth. Insertion mutations in the fsr operon affected biofilm formation on two distinct abiotic surfaces. Inactivation of the fsr-controlled gene gelE encoding the zinc-metalloprotease gelatinase was found to prevent biofilm formation, suggesting that this enzyme may present a unique target for therapeutic intervention in enterococcal endocarditis.